Age-appropriate vaccination coverage and its determinants in children aged 12-36 months in Nepal: a national and subnational assessment - Santosh Kumar Rauniyar; Yoko Iwaki; Daisuke Yoneoka; Masahiro Hashizume; Shuhei Nomura (BMC, 2021)
Abstract Background Vaccination is one of the effective ways to develop immunity against potential life-threatening diseases in children in early age. This study is focused on analysing the age-appropriate vaccination coverage at national and subnational levels and identify the factors associated with age-appropriate coverage in Nepal. Methods 460 children aged 12-36 months were included in the study. The data was obtained from Nepal Demographic and Health Survey (NDHS) 2016-17. Age-appropriate coverage of Bacillus Calmette-Guerin vaccine (BCG), oral polio vaccine (OPV) doses 1-3, pentavalent vaccine (PE) doses 1-3, and first dose of measles, mumps, and rubella vaccine (MMR) were estimated using Kaplan Meier method. Multilevel logistic regression with random intercept was used to identify the factors associated with age-appropriate vaccination. Results The crude coverage of the vaccines included in the study ranged from 91.5% (95% CI, 88.5-93.7) for PE3 to 97.8% (95.8-98.7) for BCG. Although the crude coverage of all the vaccines was above 90%, the age-appropriate coverage was significantly low, ranging from 41.5% (36.5-46.6) for PE3 to 73.9% (69.2-78.1) for PE1. Furthermore, high disparity in timely vaccination coverage was observed at regional level. Compared to the age-appropriate vaccination coverage in other provinces, Province 2 had the lowest coverage of all, followed by that in Province 6. The timeliness of vaccination was significantly associated with subnational regions i.e., provinces and the season of childbirth. Conclusion Although the immunization program in Nepal has achieved the target of 90% crude coverage of all the childhood vaccines, the age-appropriate coverage is significantly low which undermines the effectiveness of the vaccines administered. Thus, along with crude coverage, timeliness of the vaccines administered should be taken into consideration and thoroughly monitored at national and subnational levels. Provincial government should formulate tailored strategies to ensure the timely administration of the childhood vaccines.